Risk Factors, Prevalence and Assessment of the Degree of Pelvic Organ Prolapse: A Comparative Study in Secondary Level Hospital in Nepal - Gautam, Sumitra; Lamsal, Dinesh Kumar; Rimal, Usha (Nepal Journal of Health Sciences, 2026)
Introduction: Pelvic organ prolapse is the commonest morbidity worldwide. It is one of the leading reproductive health problems among Nepalese women, particularly among the women in rural Nepal. Objective: To determine the prevalence, associated risk factors, and degree of pelvic organ prolapse among women attending a secondary level hospital in Nepal. Methods: A comparative cross-sectional study was conducted at Bhaktapur Hospital, from January to June 2023. A total of 256 women aged 40-60 years were enrolled in the study consisting of 121 in study group and 135 in control group using purposive sampling method. Pessary use, past medical and surgical history, obstetric and nonobstetric risk factors were noted. General, systemic, and pelvic examinations were part of the clinical evaluation, and pelvic organ prolapse was graded using the simplified Pelvic Organ Prolapse Quantification system. Frequencies of variables were calculated, and comparisons between groups were evaluated using chi square tests. Results: The prevalence of pelvic organ prolapse was 17.82% among women aged 40-60 years, while it was 3.09% among all gynecological cases. Risk factors such as age at first vaginal birth <20 years, multiparity, vaginal delivery, short pregnancy gap, home birth of large infants, smoking, and insufficient postpartum rest, were identified. Common symptoms were something coming out per vagina (98.3%), heaviness in vagina (96.7%), feeling of lump at introitus (95.9%), Backache/dragging sensation (59.5%) and chronic cough/respiratory infection (56.2%). Majority (54.55%) had stage III prolapse and multi- compartment prolapse (43.8%). Conclusions: Raising awareness about delaying marriage and childbirth, contraceptive use, adequate rest, and proper nutrition may help reduce pelvic organ prolapse burden. Keywords: Pelvic organ prolapse; risk factor, Nepal.